Antibacterial Effects of the Novel Blue Laser and Erbium Chromium Laser on Enterococcus Faecalis in Root Canal Dentin with Different Thicknesses - Seyedeh Sareh Hendi; Erfan Ahmadyani; Mohammad Yousef Alikhani; Maryam Farhadian; Alireza Mirzaei (International Journal of Dentistry)
The aim of this study was to investigate the antibacterial effects of 445 nm blue diode lasers and erbium chromium lasers on the biofilm of Enterococcus faecalis in root canal dentin with different thicknesses. Dentin slices with thicknesses of 300, 500, and 1,000 microns were prepared; and after the biofilm formation, they were randomly divided into four groups: group A : Er, Cr:YSGG laser radiation; group B: 445 nm diode laser radiation; group C : laser radiation in three cycles; and control group D: 5 samples of each thickness were selected as a positive control group. Er, Cr:YSGG and diode lasers alone did not significantly reduce the number of bacteria in any of the thicknesses. Only in 1 mm thick sections, the group exposed with the both Er, Cr:YSGG laser and 445 nm diode laser (66%) significantly reduced the number of bacteria. There was a significant difference in a thickness of 0.3 mm compared to a thickness of 1 mm, indicating that these lasers had a better effect at a thickness of 0.3 mm than at 1 mm parts (P-value < 0.008). It seems that these lasers can be used as an adjunct to conventional chemical methods in cleaning infected canals.